О наилучших тригонометрических приближениях и колмогоровских поперечниках классов Бесова функций многих переменных - Романюк, А.С. (Український математичний журнал, 1993)
The order estimates for the best trigonometric approximations and the Kolmohorov diameters of the classes Brp,θ of functions of many variables in the space Lq are obtained for certain values of the parameters p,q.